Users of the Information in the archive: perspectives of approximation and application in the field of studies of Information Science - Dorado Santana, Yanara (2018)
The user studies are an important management tool, which aims to identify the user profile, its informational needs, and the satisfaction with the services offered by a given unit of information. The present investigation deals with a discussion about the studies of users applied to the archive contemplating an approach with the Information Science. The research is a first theoretical approach to the phenomenon of user studies, for an upcoming research to develop a proposal of user studies for the National Archive of Angola. In the same way, it aims to examine the theoretical conceptual elements regarding the studies of information users in archival information units. In this article we present a bibliographical review comprising general aspects, about information users, information needs and study of file users. An analysis of pertinent bibliographies with the same object of study is anchored to studies of information users focusing on archival users. As a problem the starting question defines how it is possible to think of applications of study of users in the ambit of the Archivology and of the archive from a dialogue with the assumptions of the Information Science?. Conclusions are presented result of the study and realized analysis.